Perlindungan Penduduk Sipil Dari Kelompok Kriminal Bersenjata Di Provinsi Papua Ditinjau Dari Hukum Humaniter Internasional - Chrisdian Balandina Hitipeuw; Marthinus Kainama; Richard Marsilio Waas (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Civil protection in Papua Province from Armed Criminal Groups (KKB) must be a serious concern, considering the cruel actions carried out by the KKB starting from shootings, persecution, arson and various other forms of crime that have caused casualties and property that have continued since to year.Purposes of the Research: to know the regulation of non-international armed conflict and how to protect the civilian population from KKB in Papua Province. Methods of the Research: This legal research, the author uses normative research. That is, a study that primarily examines positive legal provisions, legal principles, and legal doctrines to answer legal questions faced.Results of the Research: The results show that the regulation of non-international armed conflicts can be found in the Geneva Convention of 1949 article 3 regarding armed conflicts that are not international in nature in which one of the major participants is required to comply with the provisions regarding protected persons in the event that they are not actively engaged in hostilities. Furthermore, regarding the protection of the civilian population in Papua Province based on a review of humanitarian law so far it cannot be applied, because the conflict conditions in Papua Province cannot yet be categorized as non-international conflicts, but are classified as situations of domestic security disturbances or internal disturbances and tensions. Thus national law and international human rights law apply.